Clinical characteristics, treatment and prognosis of infants with retinoblastoma: a multicenter, 10-year retrospective analysis - Yi Zhang; Yizhuo Wang; Tian Zhi; Mei Jin; Dongsheng Huang; Xiaoli Ma (BMC, 2023)
Abstract Background To summarize the characteristics and treatment, and analyze the prognosis of large number of infants with retinoblastoma (RB) in China through a multicenter, 10-year retrospective analysis. Methods The data of RB infants were collected from multiple centers. The characteristics and survival prognosis were analyzed. The overall survival (OS) rate was estimated by the Kaplan-Meier method. Multivariate Cox survival analysis was to evaluate the independent risk factors affecting the prognosis of RB infants. Results A total of 373 RB infants (202 boys and 171 girls) were included, the median age was 6.22 months (10 days to 11.93 months). The median follow-up time of RB infants was 18.4 (1.02-122.81 months). After excluding the lost to follow-up cases, the OS rate was 97.7% (345/353). Kaplan-Meier survival analysis indicated that 9 cases died and the median survival time was not reached. Univariate analysis of prognostic factors revealed eye affected, presenting signs, left eye stage and recurrence to be poor prognostic factors for OS rate in RB infants (all P < 0.05). Multivariate Cox regression analyses for OS showed recurrence (HR = 1.376, 95% CI: 0.878-2.156, P = 0.048) was an independent factor for prognosis of infants with RB. The median survival time of infants underwent chemotherapy + intra-arterial chemotherapy (IAC) + enucleation + vitrectomy was the longest than other treatments (n = 9, 47.64 months, OS = 100%, all P < 0.05). There was a history of RB in 17 infants' lineal relatives. Kaplan-merier survival analysis indicated 1 case died and the median survival time was not reached. Conclusion Recurrence is an independent factor for prognosis of RB infants, which still needs attention after treatment. Early screening, comprehensive treatments and follow-up of patients may lead to improvements of prognosis of RB infants.